Catur Purusa Artha Memoderasi Pengaruh Good Corporate Governance dan Komitmen Organisasi terhadap Kinerja LPD - Suparsa, I Made; Werastuti, Desak Nyoman Sri; Diatmika, I Putu Gede (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
The aim of this research is to analyze the influence of good corporate governance and organizational commitment on LPD performance with Catur Purusa Artha as a moderating variable. This research uses an empirical study strategy. The approach used in this research is a quantitative approach. This type of research uses explanatory research. The population in this study were all LPD employees who were still actively operating in Gianyar Regency, totaling 1,709 people. Sampling in this research used a non-probability sampling method with a purposive sampling technique. The number of samples in this study was 249 LPD Chairmen. The data analysis method in this research uses descriptive statistical analysis and Structural Equation Modeling analysis with the Partial Least Square (PLS) approach with the support of SmartPLS 4.0 software. The results of hypothesis testing are that good corporate governance and organizational commitment have a positive effect on LPD performance. Catur Purusa Artha does not moderate the influence of good corporate governance on LPD performance. Catur Purusa Artha strengthens the influence of organizational commitment on LPD performance.